Does attention training induce any changes in the level of the selected cognitive processes in handball players - Szczypinska, M.; Mikicin, M. (Journal of Physical Education and Sport, 2019)
Problem Statement The goal of the paper is to analyse the changes in the level of attention, peripheral perception and sensorimotor coordination in male and female handball players following neurofeedback-EEG trainings. Handball involves direct fight with the opponent, which requires proper mental preparation. The discipline is becoming more and more dynamic, thus the player needs to make quick decisions based on sudden events and their own psychomotor abilities. Approach The study involved 18 athletes (9 women - 1st league, 9 men - 2ndleague) AZS AWF Warsaw in handball. The Vienna Test System was applied: a test to measure attention (COG), peripheral perception (PP-R) and sensorimotor coordination (SMK). Measurements were performed before and after 20 neurofeedback-EEG trainings (training took place twice a week). Each 30-minute training (8 rounds, 3 minutes each with a 30-second break following every round). Results The differences between the first and second measurement indicate that the male and female handball players subject to the analysis improved their general attention level. The subjects performed a task more precisely in the course of the second measurement (p<0.05). Significant differences (p<0.05) were also noted in the level of sensorimotor coordination. The subjects improved eye-hand-leg coordination. In the case of peripheral perception, significant differences (p<0.05) were observed only in the group of men. Conclusions The neurofeedback-EEG training improved the attention and sensorimotor coordination of male and female handball players as well as peripheral perception in male handball players.